Artificial Intelligence Implementation in E-Marketing: A Systematic Literature Review and Bibliometric Analysis - Yohannes Vemberi; Tri Gunarsih; Lucia Ika Fitriastuti; Fransius Awaldo Damanik (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Artificial Intelligence (AI) has recently gained considerable attention and is being increasingly applied across various fields. One of the most rapidly growing areas is marketing, particularly in the development of e-marketing in many companies. The purpose of this article is to review various studies related to artificial intelligence and e-marketing by presenting a comprehensive discussion.  The reviewed works consist of 82 studies published between 2018 and 2025. The data analysis focuses on methods applied, findings, strengths, and limitations. In addition, a bibliometric analysis was conducted to complement the review. A total of 500 articles related to artificial intelligence implementation in e-marketing were collected from Google Scholar, Emerald, Elsevier, ScienceDirect, and Scopus, and processed using VosViewer to support the findings. The combined analysis highlights key challenges and identifies future research opportunities in the field of artificial intelligence and e-marketing. Results from studies highlight several benefits of AI, including its potential to revolutionize marketing strategies, introduce new innovations, enhance personalization and customer experience, optimize operational efficiency, and improve overall company performance. The results reveal various research limitations that may help future researchers develop new theoretical and methodological insights. In addition, this study provides valuable information and knowledge for companies seeking to implement artificial intelligence in e-marketing.